2022
DOI: 10.21608/eajbsf.2022.215385
|View full text |Cite
|
Sign up to set email alerts
|

Pyroligneous Acid Derived from ficus benjamina Wastes Synergize Deltamethrin against Sitophilus oryzae

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Ref. [77] also found that a combination of wood vinegar and the chemical insecticide deltamethrin was 90% effective against Sitophilus oryzae. It is important to note that the choice of control method and active ingredient depends on the target pest species, the type of commodity being protected, and factors such as safety, environmental impact, and regulatory considerations.…”
Section: Chemical Controlmentioning
confidence: 99%
“…Ref. [77] also found that a combination of wood vinegar and the chemical insecticide deltamethrin was 90% effective against Sitophilus oryzae. It is important to note that the choice of control method and active ingredient depends on the target pest species, the type of commodity being protected, and factors such as safety, environmental impact, and regulatory considerations.…”
Section: Chemical Controlmentioning
confidence: 99%
“…Recently, researchers have used wood vinegar as an antifungal and antitermitic agent. Wood vinegar has the potential for antimicrobial, antifungal and antitermitic activity, as well as insecticidal activity (Aly et al, 2022;Hashemi et al, 2014;Omulo et al, 2017;Shiny and Remadevi, 2014). For example, Desvita et al (2021) reported that wood vinegar from cocoa pod shells at 300℃-380℃ showed antimicrobial activity against Candida albicans and Aspergillus niger.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease environmental pollution, it is important to create alternative wood preservatives that are eco-friendly. Wood vinegar is a potential alternative that has various properties such as for antimicrobial, antifungal and antitermitic activity, as well as insecticidal activity (Shiny and Remadevi, 2014;Hashemi et al 2014;Omulo et al 2017;Aly et al 2022).…”
Section: Introduction and Objectivesmentioning
confidence: 99%